Persistent polyclonal B lymphocytosis with Epstein-Barr virus antibodies and subsequent malignant pulmonary blastoma. Issue 4 (April 1991) - Lawlor, E; Murray, M; O'Briain, D S; Blaney, C; Foroni, L; Sarsfield, P; Condell, D; Sullivan, F; McCann, S R
Abstract : Persistent polyclonal B lymphocytosis (PPBL), a rare benign lymphoproliferative disorder, occurred in a 25 year old woman. The lymphocytes showed the phenotype cIgM+, FMC7+, CD19+, CD20+, which was similar to that seen in Waldenstrom's macroglobinaemia, but the proliferation was repeatedly shown to be polyclonal both immunologically and by immunoglobulin gene rearrangement studies. Eleven years after presentation the patient developed a malignant pulmonary blastoma, a rare pulmonary tumour of combined epithelial and mesenchymal origin. The failure to develop a lymphoid malignancy over 11 years together with immunological and genetic evidence of polyclonality confirms that PPBL is a benign lymphoproliferative disorder. The subsequent occurrence of a nonhaemopoietic malignancy suggests that benign lymphoid proliferations, like their malignant counterparts, may predispose to the development of neoplasia. A role for Epstein-Barr virus in the pathogenesis of one or both of these rare conditions is suggested by the finding of raised Epstein-Barr viral capsid antigen titres.